Lithium ion secondary battery

By using silicon-carbon composite materials with specific structures in the negative electrode sheet of lithium-ion secondary battery and adding fluorobenzene compound A to the electrolyte, the thermal runaway problem caused by needle puncture during fast charging of lithium-ion batteries is solved, and the thermal runaway caused by needle puncture during fast charging is improved. The battery safety and cycle life are provided.

CN119133571APending Publication Date: 2024-12-13ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411362199.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Traditional fast-charging lithium-ion batteries are prone to needle puncture during charging, resulting in a sharp rise in internal temperature, affecting the safety and cycle life of the battery.

Method used

Add a silicon-carbon composite material with a specific structure to the negative electrode sheet of the lithium-ion secondary battery, and add para-substituted fluorobenzene compound A to the electrolyte to optimize the crystal structure of the silicon-carbon composite material and the composition of the electrolyte. To improve the needle puncture performance and cycle life of the battery.

Benefits of technology

It effectively reduces the risk of thermal runaway in the case of needle puncture, improves the structural stability and fast charging and circulation performance of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133571A_ABST
    Figure CN119133571A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, in particular to a lithium ion secondary battery. The battery comprises a positive plate, a negative plate and an electrolyte, the negative plate comprises a negative active material, and the negative active material comprises a silicon-carbon composite material; the silicon-carbon composite material has a first diffraction peak of a (002) crystal face at 2theta = 28.4 + / -1 degrees, and has a second diffraction peak of a (100) crystal face at 2theta = 43.4 + / -1 degrees; the half-peak width FWHM of the first diffraction peak is marked as W1 degrees, and the half-peak width FWHM of the second diffraction peak is marked as W2 degrees; w1 satisfies 0.3 < = W1 < = 10; w2 satisfies: 2 < = W2 < = 30; the electrolyte comprises a compound A shown in a formula I, R1 and R2 are independently selected from H, N, F and Cl substituted or unsubstituted alkyl and alkoxy with the carbon atom number of 1-6, at least one of R1 and R2 contains F, the needling performance of the battery can be effectively improved, and the cycle life of the battery can be prolonged. Formula I: # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium ion secondary battery. Background Art

[0002] Lithium-ion battery technology is developing rapidly and has become the core force of energy storage, but it also faces multiple challenges. With the popularity and increasing functionality of mobile devices such as smartphones and tablets, the power consumption of these devices has also increased. Traditional slow charging methods can no longer meet users' demand for fast charging. Fast-charging lithium-ion batteries are currently facing a series of severe challenges. On the technical level, how to shorten the charging time while ensuring that the battery's energy density, cycle life and safety are not affected is the primary problem. High-power fast charging causes the internal temperature of the battery to rise sharply when a puncture occurs, which puts higher requirements on the battery's puncture safety performance, and it is necessary to effectively improve the puncture safety to prevent thermal runaway and accelerated battery aging.

[0003] Therefore, the development of fast-charging lithium-ion batteries with high safety performance not only requires the rapid migration of lithium ions, but also ensures that the battery can dissipate heat in time when a puncture occurs to prevent thermal runaway caused by excessive temperature. Summary of the invention

[0004] The object of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a lithium-ion secondary battery, wherein a silicon-carbon composite material with a specific structure is added to a negative electrode sheet, wherein the silicon-carbon composite material has a first diffraction peak and a second diffraction peak; and a compound A is added to an electrolyte. When the half-width at half maximum FWHM of the first diffraction peak and the half-width at half maximum FWHM of the second diffraction peak of the silicon-carbon composite material and the mass proportion of compound A in the electrolyte meet a specific relationship, the acupuncture performance of the battery can be effectively improved and the cycle life of the battery can be increased.

[0005] In order to achieve the above object, the present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0006] The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a silicon-carbon composite material; the silicon-carbon composite material has a first diffraction peak of a (002) crystal plane at 2θ=28.4±1°, and a second diffraction peak of a (100) crystal plane at 2θ=43.4±1°; the half-peak width FWHM of the first diffraction peak is recorded as W1°, and the half-peak width FWHM of the second diffraction peak is recorded as W2°; W1 satisfies: 0.3≤W1≤10; W2 satisfies: 2≤W2≤30;

[0007] The electrolyte includes a compound A shown in Formula I; Formula I: Wherein, R1 and R2 are independently selected from hydrocarbon groups and hydrocarbonoxy groups having 1 to 6 carbon atoms and substituted or unsubstituted with H, N, F, and Cl, and at least one of R1 and R2 contains F.

[0008] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0009] The lithium-ion secondary battery provided by the present invention has a silicon-carbon material with a specific structure added to the negative electrode sheet, wherein the silicon-carbon composite material has a first diffraction peak at 2θ=28.4±1° and a second diffraction peak at 2θ=43.4±1°; adding compound A represented by formula I to the electrolyte can effectively improve the acupuncture performance of the battery and increase the cycle life of the battery.

[0010] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 Shown is an X-ray diffraction (XRD) spectrum of the silicon-carbon composite material of the present invention. DETAILED DESCRIPTION

[0012] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0013] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0014] Glossary

[0015] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.

[0016] In the present invention, the term "hydrocarbon group" refers to a group formed by replacing the hydrogen atom in a hydrocarbon with other groups (such as an alkyl group, a halogen atom, a hydroxyl group, a nitro group, etc.).

[0017] In the present invention, the term "hydrocarbyloxy group", also known as "alkoxy group", refers to a group formed by connecting a hydrocarbon group to an oxygen atom.

[0018] The present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0019] The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a silicon-carbon composite material; the silicon-carbon composite material has a first diffraction peak of a (002) crystal plane at 2θ=28.4±1°, and a second diffraction peak of a (100) crystal plane at 2θ=43.4±1°; the half-peak width FWHM of the first diffraction peak is recorded as W1°, and the half-peak width FWHM of the second diffraction peak is recorded as W2°; W1 satisfies: 0.3≤W1≤10; W2 satisfies: 2≤W2≤30;

[0020] The electrolyte includes a compound A shown in Formula I; Formula I: Wherein, R1 and R2 are independently selected from hydrocarbon groups and hydrocarbonoxy groups having 1 to 6 carbon atoms and substituted or unsubstituted with H, N, F, and Cl, and at least one of R1 and R2 contains F.

[0021] Exemplarily, the half-width FWHM (W1°) of the first diffraction peak can be, for example, 0.3°, 0.6°, 1°, 2°, 3°, 4°, 5°, 6°, 7°, 8°, 9°, 10° or any point value in the range consisting of any two of the above point values; the half-width FWHM (W2°) of the second diffraction peak can be, for example, 2°, 4°, 6°, 8°, 10°, 12°, 14°, 16°, 18°, 20°, 22°, 24°, 26°, 28°, 30° or any point value in the range consisting of any two of the above point values.

[0022] Exemplarily, in an X-ray diffraction (XRD) spectrum, a method for measuring the half-width of a diffraction peak may include the following steps: first, connect the lowest points on the left and right sides of the characteristic peak to form a baseline L1; then, draw a straight line L2 perpendicular to the horizontal axis at the maximum diffraction intensity of the characteristic peak (the maximum diffraction intensity is denoted as I1), and the diffraction intensity at the intersection with L1 is denoted as I2; draw a straight line L3 parallel to the horizontal axis with a diffraction intensity of (I1+I2) / 2, and the 2θ values ​​of the two points on the left and right of the intersection of L3 and the characteristic peak are denoted as θ1 and θ2, respectively, then the half-width of the diffraction peak W=θ2-θ1.

[0023] The present invention adds the silicon-carbon composite material having a specific structure to the negative electrode sheet, and the X-ray diffraction (XRD) spectrum of the silicon-carbon composite material is as follows: Figure 1As shown, compared with the traditional silicon-carbon composite material, the silicon and carbon in the silicon-carbon composite material of the present invention have a suitable degree of amorphism, can optimize the crystal structure, have a smaller grain size, a larger peak width, and fewer lattice defects. Due to fewer lattice defects, the silicon-carbon composite material can guide the uniform deposition of lithium ions and inhibit the growth of lithium dendrites, thereby improving the structural stability of the battery. When subjected to external impacts such as needle puncture, the positive and negative electrodes of the battery are short-circuited, resulting in a large amount of heat generation. Because the silicon-carbon composite material described in the present invention improves the stability of the negative electrode material, can reduce the short-circuit current, and is not easy to react at high temperatures, thereby reducing the heat generation and reducing the risk of thermal runaway; and the crystal structure with fewer lattice defects can reduce the resistance to electron transmission and more effectively control the release and diffusion of heat, so the present invention can improve the needle puncture performance of the battery; at the same time, due to the small grain size of the silicon-carbon composite material, it can also increase the contact area with the electrolyte, increase the rate of lithium ion extraction and insertion, and thus improve the fast charging cycle performance of the battery.

[0024] The present invention further studies and finds that, due to the small grain size of the silicon-carbon composite material, the grains are arranged compactly, and when expansion occurs during the cycle, the space that can expand is also smaller, and the stress on other particles is greater, thereby generating greater mechanical stress, resulting in structural damage and capacity attenuation of the negative electrode material. In order to further solve the above-mentioned problems caused by the small grain size of the silicon-carbon composite material, the present invention further adds the compound A shown in Formula I to the electrolyte. The compound A shown in Formula I is a para-substituted fluorobenzene derivative. Because it is para-substituted, the interaction between the two substituents is weak, and the electron cloud density of the benzene ring is less affected, which is conducive to maintaining the stability of the benzene ring. In the electrolyte, the benzene ring is not easy to decompose and open the ring, so that the compound A can form a more stable protective film (SEI film) on the surface of the negative electrode material, thereby reducing the mechanical stress of the battery, inhibiting the expansion of the battery, and at the same time, it can reduce the growth rate of the AC internal resistance ACIR and the DC internal resistance DCIR of the battery, more effectively protecting the integrity of the structure of the negative electrode material, and at the same time, the compound A forms a more stable SEI film to inhibit the side reaction of direct contact between the electrolyte and the electrode material, and improve the cycle stability of the battery.

[0025] In summary, the present invention can effectively improve the acupuncture performance of the battery, and increase the cycle life and fast charging performance of the battery by adding the silicon-carbon composite material with a special structure into the negative electrode material and adding compound A into the electrolyte.

[0026] In some embodiments, W1 and W2 satisfy: 3≤W1+W2≤35, W2>W1, and the value of W1+W2 can be, for example, 3, 6, 10, 15, 20, 25, 30, 35 or any point value in the range composed of the above two point values; adjusting W1 and W2 to further satisfy the above relationship can further optimize the crystal structure of the silicon-carbon composite material, further reduce lattice defects, make lithium ion deposition more uniform, and inhibit lithium dendrite growth, thereby further improving the structural stability of the battery, reducing the risk of thermal runaway, and further improving the battery's needle puncture performance; avoiding W1 and / or W2 being too large will cause greater damage to the structural stability of the battery during the cycle, which will significantly reduce the battery cycle life.

[0027] In some embodiments, in compound A shown in formula I, R1 and R2 are independently selected from H, N, F, Cl substituted or unsubstituted hydrocarbon groups with 1-6 carbon atoms (for example, alkyl groups with 1-6 carbon atoms, alkenyl groups with 1-6 carbon atoms, alkynyl groups with 1-6 carbon atoms), alkoxy groups with 1-6 carbon atoms, and at least one of R1 and R2 contains F.

[0028] In some embodiments, in the compound A shown in Formula I, R1 and R2 are independently selected from H, N, F substituted or unsubstituted alkyl, alkenyl, alkynyl, alkoxy with 1-4 carbon atoms, and both R1 and R2 contain F. Compound A further satisfies the above conditions, and compound A is a para-substituted fluorobenzene derivative that can make the protective film formed on the electrode surface more uniform and stable, further reduce the AC internal resistance ACIR and DC internal resistance DCIR growth rate of the battery, reduce the expansion rate of the battery, and further improve the cycle stability of the battery.

[0029] In some embodiments, based on the total mass of the electrolyte, the mass proportion of compound A is recorded as x%; x satisfies: 0.1≤x≤5, and the mass proportion of compound A x(%) can be, for example, 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any point value in the range composed of the above two point values. When the mass proportion of compound A is adjusted to further meet the above range, the structural destruction and capacity attenuation problems of the negative electrode material caused by the small grain size of the silicon-carbon composite material can be better solved, and the battery structure can be stabilized; when the content of compound A is too much, the film is too thick, resulting in an increase in interface impedance, which in turn leads to deterioration of battery cycle performance.

[0030] In some embodiments, compound A shown in formula I includes at least one of the following compounds:

[0031]

[0032] The silicon-containing substances in the negative electrode materials are mainly silicon-carbon composite materials. The higher the silicon content in the negative electrode material and the greater the silicon-carbon composite material content, the higher the theoretical capacity of the negative electrode material will be. However, the volume change of the silicon-containing negative electrode material during the charging and discharging process will be more significant, which will cause the negative electrode material particles to be crushed, the active material to be separated from the current collector, and the formation of an unstable solid electrolyte interphase (SEI) film. The rupture of the SEI film will lead to the continuous consumption of the electrolyte, thereby greatly affecting the cycle stability and performance of the battery.

[0033] In some embodiments, W1, W2, and x satisfy: 0<2x / (W1+W2)≤3. For example, the value of 2x / (W1+W2) can be, for example, 0.01, 0.5, 1, 1.5, 2, 2.5, 3, or any point value in the range of the above two point values, preferably 0<2x / (W1+W2)≤1. The present invention uses a silicon-carbon composite material with a specific structure in combination with compound A, and adjusts W1, W2, and x to meet the above conditions, which can further improve the battery needle puncture performance, as well as improve the battery cycle stability and fast charging performance.

[0034] The present invention further provides: the electrolyte includes a lithium salt; the mass percentage of the lithium salt is y% based on the total mass of the electrolyte; the content of silicon in the negative electrode active material is z%; y and z satisfy: 0<z / y≤2. Exemplarily, the value of z / y can be, for example, 0.01, 0.1, 0.4, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2 or any point value in the range of any two of the above point values.

[0035] Compared with the traditional electrolyte lithium salt addition amount in the prior art, the electrolyte of the present invention has a higher lithium salt content. When W1, W2, and x satisfy: 0<2x / (W1+W2)≤3, when the mass proportion of lithium salt y% and the content of silicon element z% further satisfy the above range, there are more free lithium ions in the electrolyte, which can improve the ionic conductivity of the electrolyte, improve the charging and discharging efficiency of the battery, and improve the fast charging performance of the battery; increasing the lithium salt content in the electrolyte can increase the concentration of the electrolyte, thereby helping to form a more stable SEI film, improve the structural stability of the negative electrode material, and reduce the decomposition of the electrolyte and the consumption of active lithium; high-concentration electrolyte can also slow down the damage to the SEI film caused by the volume expansion of the silicon-containing negative electrode material during the charging and discharging process, thereby improving the cycle stability of the battery.

[0036] In some embodiments, the mass proportion y(%) of lithium salt in the electrolyte satisfies: 20≤y≤30, and the mass proportion y(%) of lithium salt can be, for example, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% or any point value in the range formed by any two of the above point values. An increase in the mass proportion of lithium salt will increase the number of mobile lithium ions in the battery, increase heat generation, and reduce the safety performance of the battery, but can increase the cycle life of the battery; a decrease in the mass proportion of lithium salt will reduce the fast charging performance of the battery, deteriorate the cycle life of the battery, and the strength of the formed SEI film will also decrease, resulting in degradation of safety performance.

[0037] In some embodiments, the content ratio z(%) of silicon in the negative electrode active material satisfies: 0<z≤50, and the content ratio z(%) of silicon can be, for example, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or any point value in the range of the above two point values. The greater the content ratio of silicon, the stronger the stress effect on the SEI film, and the deterioration of the cycle and safety performance; while the reduction of silicon content will reduce the capacity of the battery, and the number of lithium ions that can be embedded and extracted during the charge and discharge process will be significantly reduced. Under the conditions of the high lithium salt electrolyte of the present invention, lithium precipitation will be more likely to occur, significantly reducing the battery cycle life.

[0038] When W1, W2, and x satisfy: 0<2x / (W1+W2)≤3, and y and z satisfy: 0<z / y≤2, and when y and / or z are adjusted to further satisfy the above range, the ionic conductivity of the electrolyte can be further improved, the charge and discharge efficiency of the battery can be improved, the fast charging performance of the battery can be improved, a more stable SEI layer can be formed, and the decomposition of the electrolyte and the consumption of active lithium can be reduced; while providing a higher energy density, the structural stability of the negative electrode material can be further improved, and the cycle stability of the battery can be improved.

[0039] For example, the content ratio of the silicon element in the negative electrode active material can be tested by thermogravimetric analysis, for example, using a Shimadzu DTG-60 thermogravimetric analyzer for testing, and the test conditions include: sample weight 5 mg, air as atmosphere, heating rate 10 ° C / min from room temperature to 900 ° C and constant temperature for 40 minutes. The relationship between the mass ratio of silicon-carbon material (denoted as x) and the final weight residual percentage of the entire test (denoted as y) is: x = 7y / 15.

[0040] In some embodiments, the lithium ion electrolyte further includes a lithium salt, which may be selected from lithium hexafluorophosphate (LiPF6), lithium bisfluorosulfonyl imide (LiFSI), lithium difluorophosphate (LiPO2F2), lithium hexafluoroantimonate (LiSbF6), lithium hexafluoroarsenate (LiAsF6), lithium bistrifluoromethylsulfonyl imide (LiTFSI), lithium trifluoromethyl sulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyl lithium or lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate (LiDFOB), lithium difluorobisoxalatophosphate, lithium tetrafluoroborate (LiBF4), lithium bis(difluorophosphoryloxy)difluoroborate, lithium tetrakis(difluorophosphoryloxy)borate. One or more.

[0041] Preferably, the lithium salt is a combination of LiFSI and LiPF6; further, the mass ratio of LiFSI and LiPF6 is 1:(1.5-4), and the mass ratio of LiFSI and LiPF6 can be, for example, 1:1.5, 1:2, 1:2.5, 1:3, 1:4 or any point value in the range consisting of any two of the above point values.

[0042] The inventors of the present invention have found through further research that, since the electrolyte of the present invention contains a higher lithium salt content than the traditional electrolyte, while significantly improving the battery performance, it also brings about the problem of significantly increasing the viscosity of the electrolyte, enhancing the interaction between ions, increasing the resistance to ion migration, and increasing the heat generation of the battery. To further solve this problem, the present invention further proposes that: the electrolyte also includes compound B shown in formula II, and / or compound C shown in formula III;

[0043] Formula II: Wherein, R3 and R4 are independently selected from H, O, halogen-substituted or unsubstituted hydrocarbon groups with 1 to 6 carbon atoms;

[0044] Formula III: Wherein, R5, R6, and R7 are independently selected from H, O, and a halogen-substituted or unsubstituted hydrocarbon group having 1 to 10 carbon atoms.

[0045] In some embodiments, the electrolyte may be further added with a compound B shown in formula II, a compound C shown in formula III, or a combination of compound B shown in formula II and compound C shown in formula III, preferably compound B shown in formula II and compound C shown in formula III.

[0046] The present invention further adds a compound B shown in formula II to the electrolyte, wherein the compound B has a relatively low viscosity and good solubility in lithium salts, and the compound B has a compact and orderly chemical structure, the distance between atoms in the molecule is moderate, and the compound B has stable chemical bonds. Under the premise that W1, W2, and x satisfy: 0<2x / (W1+W2)≤3, and y and z satisfy: 0<z / y≤2, the further addition of the compound B can maintain a relatively low viscosity of the electrolyte when the lithium salt concentration in the electrolyte is high through its own relatively low viscosity characteristics and good solubility in lithium salts; the distance between atoms in the compound B molecule is moderate, the chemical structure is compact and orderly, and the formed stable chemical bonds can effectively promote collision and vibration heat transfer between molecules during the heat transfer process, reduce heat accumulation of the battery, extend the service life of the battery, and improve the battery safety.

[0047] The present invention further adds a compound C shown in Formula III to the electrolyte, wherein the phosphate group at the core of the compound C is a hydrophilic group and the outside is a hydrophobic group, so that it has both hydrophilic and hydrophobic groups, and can better infiltrate with various media phenotypes. The compound C forms a lyophilic protective layer on the surface of the positive and negative electrodes of the battery, which can guide the electrolyte to spread and infiltrate better on the electrode surface, improve the lithium precipitation problem at the electrode interface, and increase the battery cycle life. Moreover, the protective layer formed by the compound C has good thermal stability and is difficult to break even at high temperatures, which prevents side reactions between the electrode and the electrolyte, protects the structural stability of the electrode material, and can also improve the hot box safety performance of the battery.

[0048] In summary, when y and z satisfy: 0<z / y≤2, further adding compound B shown in formula II and compound C shown in formula III to the electrolyte can avoid the problems of increased viscosity and resistance of the electrolyte due to the high concentration of lithium salt in the electrolyte, further maintain the structural stability of the negative electrode material, improve the battery cycle life, and improve the safety performance of the battery hot box.

[0049] In some embodiments, based on the total mass of the electrolyte, the mass proportion of compound B is recorded as m%, and the mass proportion of compound C is recorded as n%; m ​​and n satisfy: 0<n / m≤1. Exemplarily, the value of n / m can be, for example, 0.01, 0.03, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 or any point value in the range of the above two point values. When y and z satisfy: 0<z / y≤2, the mass proportions of compound B and compound C added to the electrolyte satisfy the above relationship, the viscosity of the electrolyte can be further reduced, the structural stability of the negative electrode material can be improved, the heat accumulation of the battery can be reduced, the cycle life of the battery can be more effectively improved, and the safety performance of the battery hot box can be improved.

[0050] In some embodiments, the mass proportion m(%) of compound B in the electrolyte satisfies: 5≤m≤70, and the mass proportion m(%) of compound B can be, for example, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or any point value in the range composed of the above two point values. When m and n satisfy: 0<n / m≤1, the mass proportion m of compound B in the electrolyte further satisfies the above range, which can avoid the problem that when m<5, the viscosity of the electrolyte is not significantly reduced, the resistance of ion migration is increased, and the heat generation of the battery is increased; when m>70, the electrolyte and the electrode interface have poor wettability, resulting in interface lithium precipitation and reduced cycle life.

[0051] In some embodiments, the mass proportion n(%) of compound C in the electrolyte is: 0<n≤5, and the mass proportion n(%) of compound C can be, for example, 0.01%, 0.03%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%. When m and n satisfy: 0<n / m≤1, the mass proportion n of compound C in the electrolyte further satisfies the above range, which can more effectively solve the problem of poor wettability of the electrolyte and electrode interface caused by adding compound B to the electrolyte, which easily leads to lithium precipitation at the interface, and further improve the hot box safety performance of the battery.

[0052] In some embodiments, the compound B shown in Formula II includes at least one of the compounds shown below:

[0053]

[0054] In some embodiments, the compound C shown in formula III includes at least one of the compounds shown below:

[0055]

[0056]

[0057] When m and n satisfy: 0<n / m≤1, further selecting the above-mentioned compound B and / or compound C can further improve the structural stability of the negative electrode material, the cycle life of the battery and the hot box safety performance of the battery.

[0058] In some embodiments, the silicon-carbon composite material is doped with N element and / or P element. Further doping the silicon-carbon composite material with N element and P element can make the surface of the negative electrode material polar, so that it interacts with the solvent molecules in the electrolyte, promotes the film-forming reaction rate of compound A on the electrode surface, and forms a more stable SEI film with low interface impedance under the action of N element and P element in the negative electrode material, thereby improving the charge and discharge performance of the battery.

[0059] In some embodiments, in the silicon-carbon composite material, the content of N element is ≤6%, and the content of N element can be, for example, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 5.9% or any point value in the range of the above two point values, preferably 2%-5%. In some embodiments, in the silicon-carbon composite material, the content of P element is 0.05%-6%, and the content of P element can be, for example, 0.05%, 0.08%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6% or any point value in the range of the above two point values, preferably 1%-5%. The content of N and P elements further meets the above range, which can further promote the film-forming reaction rate of compound A on the electrode surface and improve the charge and discharge performance of the battery. Avoid excessive content of N and P elements, which will increase the polarity of the electrode material and the force on the solvent molecules, making the film on the electrode surface thicker and increasing the solvent consumption, causing the battery cycle life to decrease.

[0060] In some embodiments, the silicon-carbon composite material may be doped with only N element, only P element, or both N element and P element, preferably N element and P element.

[0061] In order to further reduce the volume change of silicon-containing negative electrode materials and reduce the large mechanical stress generated inside the battery, the present invention further proposes: the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector; a recessed area is disposed on the positive electrode active material layer; the depth of the recessed area is recorded as bμm, and b satisfies: 5≤b≤25. Exemplarily, the depth b (μm) of the recessed area can be, for example, 5μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 22μm, 24μm, 25μm or any point value in the range consisting of two of the above point values.

[0062] A recessed area is provided on the positive electrode active material layer. For example, an embossing pattern can be formed by using a positive electrode sheet embossing process, that is, a recessed area is formed. The recessed area is provided on the positive electrode active material layer, which can effectively prevent the positive electrode material from being squeezed or stretched when the mechanical stress is transmitted to the positive electrode through the internal structure of the battery, thereby causing cracks or pulverization, causing the binding force between the active material and the current collector in the positive electrode material to weaken, and causing stratification or shedding, thereby preventing the capacity of the positive electrode material from being reduced and the cycle performance from being reduced. When the depth b (μm) of the recessed area further meets the above range, it can effectively avoid the situation when b<5, the embossing depth is too small, and the effect of improving the cycle performance is not good; it can also effectively avoid the situation when b>25, the embossing depth is too large, excessive squeezing causes the internal channel of the positive electrode material to be narrowed or broken, and the internal structure of the positive electrode material is damaged, resulting in an increase in the internal resistance of the positive electrode sheet, an increase in the energy loss of the battery during the charging and discharging process, and a reduction in the cycle life and safety performance of the battery. Therefore, by setting a recessed area b (μm) on the positive electrode active material layer, and b satisfies: 5≤b≤25, the structural stability of the positive electrode material can be further enhanced, and the battery cycle stability and cycle life can be improved.

[0063] In some embodiments, the recessed area provided on the positive electrode active material layer is an embossed pattern, and the embossed pattern is a regular or irregular pattern, preferably a regular pattern, and more preferably a honeycomb pattern. The recessed area is set as a honeycomb embossed pattern to form a microstructure similar to a honeycomb. When the negative electrode expands and generates mechanical stress, these concave and convex textures can serve as stress dispersion points to disperse the stress over a larger area, thereby reducing the direct impact on the positive electrode material, maintaining the structural integrity and performance stability of the positive electrode material, further alleviating the damage to the positive electrode material caused by mechanical stress, and improving the battery cycle stability and cycle life.

[0064] In some embodiments, the recessed area may be disposed at all or part of the positive electrode active material layer; for a wound battery, the recessed area is preferably disposed at the bend of the positive electrode sheet, the top and bottom edges of the positive electrode sheet; for a stacked battery, the recessed area is preferably disposed at the four edges of the positive electrode active material layer.

[0065] In order to further protect the positive and negative electrodes of the battery and improve the cycle performance of the battery, the present invention further proposes that: the electrolyte also includes a combination of one or more of nitrile compounds, fluoroethylene carbonate and sulfonic acid compounds. In the present invention, nitrile substances are used as positive electrode protection additives, which can prevent the dissolution of positive electrode metal ions during the cycle by complexing ions at the positive electrode, causing instability of the positive electrode structure and deterioration of the electrochemical performance; since nitrile additives are not compatible with the negative electrode, in order to further improve the battery performance, the present invention further adds fluoroethylene carbonate and sulfonic acid negative electrode protection additives to the electrolyte to form a protective film at the negative electrode to reduce the deterioration of the negative electrode by nitrile additives. Therefore, the present invention further adds a combination of one or more of nitrile compounds, fluoroethylene carbonate and sulfonic acid compounds to the electrolyte, which can effectively protect the positive and negative electrodes of the battery and improve the cycle performance of the battery.

[0066] In some embodiments, based on the total mass of the electrolyte, the mass proportion of the nitrile compound is 1%-5%, and the mass proportion of the nitrile compound can be, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any point value in the range of any two of the above points. The mass proportion of the nitrile compound further satisfies the above range, which can further prevent the dissolution of positive electrode metal ions during the cycle, stabilize the positive electrode structure, and improve the electrochemical performance of the battery.

[0067] Illustratively, the nitrile compound includes, but is not limited to, one or more of a mononitrile additive, a dinitrile additive, and a trinitrile additive.

[0068] Illustratively, the mononitrile additive includes, but is not limited to, one or more of benzonitrile, p-toluenenitrile, and 3,5-difluorobenzonitrile.

[0069] Exemplarily, the dinitrile additive includes, but is not limited to, one or more of adiponitrile (AND), succinonitrile (SN), and ethylene glycol bis(propionitrile) ether.

[0070] Illustratively, the trinitrile additive includes, but is not limited to, one or more of 1,3,6-hexanetrinitrile (HTCN), 1,2,6-hexanetrinitrile, and 1,2,3-tris(2-cyanoethoxy)propane.

[0071] In some embodiments, based on the total mass of the electrolyte, the mass proportion of fluoroethylene carbonate is 5%-20%, and the mass proportion of fluoroethylene carbonate can be, for example, 5%, 8%, 10%, 12%, 14%, 16%, 18%, 20% or any point value in the range composed of the above two points. Based on the total mass of the electrolyte, the mass proportion of sulfonic acid compounds is 0.1%-5%, and the mass proportion of sulfonic acid compounds can be, for example, 0.1%, 0.4%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any point value in the range composed of the above two points. When fluoroethylene carbonate and sulfonic acid compounds further meet the above range as negative electrode protection additives, the risk of increased battery gas production caused by excessive mass proportion of negative electrode protection additives can be avoided.

[0072] Illustratively, the sulfonic acid compounds include, but are not limited to, one or more of 1,3-propane sultone, 1-propylene-1,3-sultone, 5-methylthiothiocyanate 2,2-dioxide, 1,3-propylene sultone, 2,4-butane sultone, 1,4-butane sultone, 1,3-butane sultone, and fluorinated 1,3-propane sultone.

[0073] It should be noted that, in the present invention, the amount of the negative electrode protection additive (such as fluoroethylene carbonate, sulfonic acid compounds) should be greater than the positive electrode protection additive (nitrile compounds) to form effective protection.

[0074] In some embodiments, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes lithium cobalt oxide (LiCoO2). Further, LiCoO2 is selected as the positive electrode active material, and lithium ions can migrate quickly in the positive electrode material. The structure of the lithium cobalt oxide positive electrode material is stable, and the performance attenuation caused by changes in the material structure can be reduced during the charging and discharging process. Therefore, the use of the positive and negative electrode materials described in the present invention can not only improve the fast charging performance of the battery, but also improve the overall energy density of the battery to meet the use requirements of higher energy density.

[0075] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0076] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0077] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0078] Example 1-1

[0079] 1) Preparation of positive electrode

[0080] The positive electrode active materials lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), conductive carbon black SP (super P) and carbon nanotubes (CNT) are mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of an aluminum foil; the coated aluminum foil is dried, and then rolled and cut to obtain the desired positive electrode sheet.

[0081] 2) Negative electrode preparation

[0082] The negative electrode active materials artificial graphite, silicon-carbon composite material, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, SP and single-walled carbon nanotubes (SWCNTs) are mixed in a mass ratio of 74.5:40:2.5:1.5:1:0.5, deionized water is added, and the negative electrode active slurry is obtained under the action of a vacuum mixer; the negative electrode active slurry is evenly coated on both surfaces of the copper foil; the coated copper foil is dried at room temperature, and then transferred to an oven at 80°C for drying for 10 hours, and then cold pressed and cut to obtain the negative electrode sheet.

[0083] 3) Preparation of electrolyte

[0084] In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), EC, PC, DEC, and PP were mixed in a mass ratio of 10:20:20:50. Then, fully dried LiPF6 (15%) and LiFSI (7%) were quickly added based on y% of the total mass of the electrolyte, and after dissolution, 1% of the formula I-1 compound A was added based on the total mass of the electrolyte. Finally, 1% of ADN, 1.5% of SN, 2.5% of HTCN, 12% of fluoroethylene carbonate, and 3% of PS were added based on the total mass of the electrolyte. After stirring evenly, the desired electrolyte was obtained after passing the moisture and free acid tests.

[0085] 4) Preparation of battery

[0086] The positive electrode sheet of step 1), the negative electrode sheet of step 2) and the separator are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, and the electrolyte of step 3) is injected into the outer packaging, and a lithium ion battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes. The battery of the present invention has a charge and discharge range of 3-4.53V.

[0087] 5) Test the battery

[0088] (i) 25℃4C cycle test

[0089] The battery obtained in the embodiment and the comparative example was charged at 4C constant current at 25°C to a voltage of 4.53V, then charged at 4.53V to a current of 0.05C, left to stand for 5 minutes, and then discharged at 1C constant current to a voltage of 3.0V, which was a charge and discharge cycle. The discharge capacity of the first week of the test was x mAh, and the discharge capacity of the Nth week was y mAh; the capacity of the Nth week was divided by the capacity of the first week to obtain the cycle capacity retention rate R=y / x of the Nth week, and the number of battery cycles was recorded when the capacity retention rate of the battery was 80%.

[0090] (ii) Acupuncture performance test

[0091] The batteries obtained in the examples and comparative examples were discharged at 25°C at a current of 0.5C to a voltage of 3.0V, then charged at a constant current of 0.5C to a voltage of 4.53V, and then charged at a constant voltage of 4.53V to a current of 0.05C. The batteries were left standing for 5 minutes, and then a steel needle with a length of 100mm, a diameter of 3mm, and a taper of 15° was inserted into the middle of the battery at a speed of 25mm / s. After the test, the steel needle was retained in the battery for 5 minutes to observe whether the battery caught fire or smoked. If so, it was unqualified, and the pass rate of the puncture performance test was recorded.

[0092] (iii) Hot box performance test

[0093] At room temperature, the battery obtained in the embodiment and comparative example was charged to 4.53V at 1C constant current, left to stand for 60 minutes, and the appearance was checked and photographed. Then the temperature was raised to 132℃±2℃ at a rate of 3℃ / min±2℃ / min and maintained for 60 minutes. The sample was observed, and it was recorded as passing the test if there was no leakage, no smoke, no fire, and no explosion. Ten samples were tested for each embodiment or comparative example, and the pass rate of the hot box performance test was recorded.

[0094] Example 1-2 and Comparative Example 1-2 are carried out with reference to Example 1-1, and the main differences are shown in Table 1. In Example 1, the mass proportion of compound A in the electrolyte is changed. In Example 2, different silicon-carbon materials are used to change the half-peak width of the first and second diffraction peaks. In Comparative Example 1, ordinary silicon-carbon material (purchased from Shanghai Shanshan Technology Co., Ltd., model SG50) is used. In Comparative Example 2, compound A is not added.

[0095] Table 1

[0096]

[0097]

[0098] Note: “ / ” indicates that the corresponding parameter is not tested.

[0099] It can be seen from Table 1 that the present invention can improve the fast charging cycle performance of the battery, improve the anti-puncture performance and reduce the risk of thermal runaway by adding a silicon-carbon composite material to the negative electrode sheet; the present invention improves the cycle stability of the battery by adding compound A to the electrolyte and adjusting the addition amount of compound A; the present invention adopts a silicon-carbon composite material with a specific structure in combination with compound A, and adjusts W1, W2, and x to meet the above conditions, which can further improve the battery puncture performance, as well as improve the battery cycle stability and fast charging performance.

[0100] Example 3 was carried out in accordance with Example 1-1, and the main differences are shown in Table 2. In particular, Example 3 changed the type of compound A.

[0101] Table 2

[0102]

[0103] It can be seen from Table 2 that the present invention can achieve similar technical effects by changing the type of compound A added to the electrolyte, and can improve the cycle stability of the battery and better solve the structural damage and capacity attenuation problems of the negative electrode material caused by the small grain size of the silicon-carbon composite material.

[0104] Example 4-6 groups were carried out with reference to Example 1-1, and the main differences are shown in Table 3. Among them, in Example 4 group, the content ratio of silicon element in the negative electrode material was changed. In Example 5 group, the mass ratio of lithium salt (a combination of LiFSI and LiPF6) in the electrolyte was changed. In Example 6 group, the type of lithium salt in the electrolyte was changed, among which, in Example 6-1, only LiPF6 was added, and the proportion of lithium salt remained unchanged, which was the same as Example 1-1; in Example 6-2, only LiFSI was added, and the proportion of lithium salt remained unchanged, which was the same as Example 1-1.

[0105] Table 3

[0106]

[0107] It can be seen from Table 3 that the present invention can further improve the fast charging performance of the battery and improve the cycle stability of the battery by adjusting the mass proportion y% of the lithium salt in the electrolyte and the content proportion z% of the silicon element to further satisfy 0<z / y≤2.

[0108] Example 7-8 groups, with reference to Example 1-1, further added compound B and compound C to the electrolyte, the main differences are shown in Table 4. Among them, in Example 7 group, the mass proportion of compound B in the electrolyte was changed; in Example 7-3 group, the amount of lithium salt added was changed to LiPF6 (5%) and LiFSI (2.5%). In Example 8 group, the mass proportion of compound C in the electrolyte was changed.

[0109] Table 4

[0110]

[0111] Note: “ / ” indicates that the corresponding parameter is not tested.

[0112] As can be seen from Table 4, the present invention further adds compound B and compound C to the electrolyte and adjusts the mass proportion (m) of compound B and the mass proportion (n) of compound C in the electrolyte to satisfy 0<n / m≤1, thereby further reducing the viscosity of the electrolyte, improving the structural stability of the negative electrode material, reducing the heat accumulation of the battery, and more effectively improving the cycle life of the battery and the safety performance of the battery hot box.

[0113] Example 9 was carried out in accordance with Example 7-1, and the main differences are shown in Table 5. In Example 9, the types of compound B and compound C in the electrolyte were changed.

[0114] Table 5

[0115]

[0116]

[0117] It can be seen from Table 5 that the present invention can achieve similar technical effects by changing the type of compound B added to the electrolyte, and can extend the service life of the battery and improve the battery safety.

[0118] In Example 10, the positive electrode active material layer was further embossed with reference to Example 7-1, and the embossed pattern was a honeycomb pattern. The recessed area was set at all positions on the positive electrode active material layer, and the main differences are shown in Table 6. In Example 10, the depth of the recessed area was changed.

[0119] Table 6

[0120] Depth of depression b / μm 25℃4C cycle number / T Acupuncture test pass rate % Hot box test pass rate % Example 10-1 12 1013 8 / 10 9 / 10 Example 10-2 5 996 8 / 10 9 / 10 Example 10-3 25 988 7 / 10 7 / 10 Example 10-4 2 971 8 / 10 9 / 10 Example 10-5 30 942 6 / 10 6 / 10

[0121] It can be seen from Table 6 that the present invention can further enhance the structural stability of the positive electrode material and improve the cycle stability and cycle life of the battery by providing a recessed area in the positive electrode active material layer and adjusting the depth of the recessed area.

[0122] Example 11 group, with reference to Example 10-1, further doped P element and N element in the negative electrode silicon-carbon composite material, the main differences are shown in Table 7. In Example 11 group, the content of the doped N element or P element was changed.

[0123] Table 7

[0124]

[0125]

[0126] Note: “ / ” indicates that the corresponding parameter is not tested.

[0127] It can be seen from Table 7 that the present invention further dopes P element and N element into the silicon-carbon composite material and adjusts the content of N element and P element, which can further improve the cycle life and safety performance of the battery by promoting film formation.

[0128] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a silicon-carbon composite material; the silicon-carbon composite material has a first diffraction peak of a (002) crystal plane at 2θ=28.4±1°, and a second diffraction peak of a (100) crystal plane at 2θ=43.4±1°; the half-peak width FWHM of the first diffraction peak is recorded as W1°, and the half-peak width FWHM of the second diffraction peak is recorded as W2°; W1 satisfies: 0.3≤W1≤10; W2 satisfies: 2≤W2≤30; The electrolyte includes compound A shown in formula I; Formula I: Wherein, R1 and R2 are independently selected from hydrocarbon groups and hydrocarbonoxy groups having 1 to 6 carbon atoms and substituted or unsubstituted with H, N, F, and Cl, and at least one of R1 and R2 contains F.

2. The lithium ion secondary battery according to claim 1, characterized in that: W1 and W2 satisfy: 3≤W1+W2≤35, W2>W1.

3. The lithium ion secondary battery according to claim 1, characterized in that: In Formula I, R1 and R2 are independently selected from H, N, F-substituted or unsubstituted alkyl, alkenyl, alkynyl, alkoxyl groups having 1 to 4 carbon atoms, and both R1 and R2 contain F; Preferably, based on the total mass of the electrolyte, the mass proportion of compound A is recorded as x%; x satisfies: 0.1≤x≤5; Preferably, the compound A represented by formula I comprises at least one of the following compounds:

4. The lithium-ion secondary battery according to claim 1, characterized in that: W1, W2, and x satisfy: 0<2x / (W1+W2)≤3; preferably 0<2x / (W1+W2)≤1.

5. The lithium ion secondary battery according to claim 1, characterized in that: The electrolyte includes a lithium salt; based on the total mass of the electrolyte, the mass proportion of the lithium salt is y%; In the negative electrode active material, the content of silicon element is recorded as z%; y and z satisfy: 0<z / y≤2; Preferably, y satisfies: 20≤y≤30; and / or, z satisfies: 0<z≤50; The lithium salt is a combination of LiFSI and LiPF6, and more preferably the mass ratio of LiFSI to LiPF6 is 1:(1.5-4).

6. The lithium ion secondary battery according to claim 1, characterized in that: The electrolyte further comprises a compound B represented by formula II, and / or a compound C represented by formula III; Formula II: Wherein, R3 and R4 are independently selected from H, O, halogen-substituted or unsubstituted hydrocarbon groups with 1 to 6 carbon atoms; Formula III: Wherein, R5, R6, and R7 are independently selected from H, O, halogen-substituted or unsubstituted hydrocarbon groups having 1 to 10 carbon atoms; Preferably, based on the total mass of the electrolyte, the mass proportion of compound B is recorded as m%, and the mass proportion of compound C is recorded as n%; m, n satisfy: 0<n / m≤1; Preferably, m satisfies: 5≤m≤70; and / or, n satisfies: 0<n≤5.

7. The lithium ion secondary battery according to claim 6, characterized in that: The compound B shown in formula II includes at least one of the compounds shown below: And / or, the compound C shown in formula III includes at least one of the compounds shown below:

8. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that: The silicon-carbon composite material is doped with N element and / or P element; Preferably, in the silicon-carbon composite material, the content of N element is ≤6%, more preferably 2%-5%; Preferably, in the silicon-carbon composite material, the content of P element is 0.05%-6%, more preferably 1%-5%.

9. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector; a recessed area is disposed on the positive electrode active material layer; Preferably, the depth of the recessed area is b μm, and b satisfies: 5≤b≤25.

10. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that: The electrolyte further comprises a combination of one or more of a nitrile compound, fluoroethylene carbonate and a sulfonic acid compound; Preferably, based on the total mass of the electrolyte, the mass proportion of the nitrile compound is 1%-5%; Preferably, based on the total mass of the electrolyte, the mass proportion of fluoroethylene carbonate is 5%-20%; Preferably, based on the total mass of the electrolyte, the mass proportion of the sulfonic acid compound is 0.1%-5%.

Citation Information

Patent Citations

  • Composite silicon-carbon material and preparation method thereof

    CN118645608A

Cited By

  • Lithium-ion secondary battery

    WO2026066637A1